A case study of Saharan cyclogenesis - Thorncroft, C.D.a c; Flocas, H.A.b (Monthly Weather Review, 1997)
A case of Saharan cyclogenesis associated with the equatorward intrusion of a trough at the end of the Atlantic storm track is investigated. It is shown that a potential vorticity anomaly resulting from a baroclinic wave life cycle associated with the polar jet interacts with the low-level baroclinicity over subtropical Africa beneath the subtropical jet. It is suggested that low-latitude synoptic-scale cyclogenesis events of this type can be triggered only by upper-level potential vorticity anomalies if they have a sufficient depth scale and that the interaction may be aided by the presence of low static stability associated with a well-mixed boundary layer. A weak cold front also forms during the cyclogenesis event associated with the convergence of the baroclinicity of the polar trough front with the baroclinicity of the subtropical heat low.
cited By (since 1996)35